(untitled) - Fowler, Richard J. (New York, 2003)
This practical, field-tested text prepares students for entry-level electronics jobs. No prior knowledge of electricity is assumed; the only prerequisites are arithmetic and basic algebra. This edition retains the previous edition's logical, sequential presentation of topics in an easy-to-understand style.
Keywords: Electricity,Điện